(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1915)
This collection includes a coinage die of the fourteenth century, a medal die of the sixteenth century, and a considerable number of both coinage and medal dies of the seventeenth century. The collection contains in all 163 matrices, puncheons, and dies which can be divided into those for coins, medals, tradesmen’s tokens and sundry small punches.